Only One Moment in Time? Investigating the Dynamic Relationship of Emotions and Attention Toward Political Information With Mobile Experience Sampling. (December 2020) - Otto, Lukas P.; Thomas, Fabian; Maier, Michaela; Ottenstein, Charlotte
This article attempts to (a) investigate the relationship between distinct emotional reactions toward political information and attention toward political news and (b) analyze whether this relationship is dynamic. We use an experience sampling design to assess recipients' immediate emotional reactions and attention toward news. Participants reported their emotional reactions (anger, fear, happiness, contentment) and attentional focus directly after following a news item for eight days in a row up to five times a day via smartphone. Results indicate that anger is positively and fear negatively correlated with attention toward political news. For positive emotional reactions, happiness is not correlated with attention to news, while contentment is negatively correlated with attention and also shows a negative lagged effect on attention at a later point in time. The study shows promising ways to assess and analyze dynamic processes in everyday media consumption.